1995
DOI: 10.1002/jcp.1041630105
|View full text |Cite
|
Sign up to set email alerts
|

Laminin decreases PRL and IGFBP‐1 expression during in vitro decidualization of human endometrial stromal cells

Abstract: The expression of laminin, a major constituent of endometrial cell basement membranes, is increased during differentiation of human endometrial stromal cells (decidualization). To determine whether laminin plays a role in decidualization, we studied the effects of laminin substrate on the synthesis and release of prolactin (PRL) and insulin-like growth factor binding protein-1 (IGFBP-1), two major secretory proteins of decidualized stromal cells. Endometrial stromal cells were plated on laminin as well as seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 31 publications
(36 reference statements)
0
14
0
1
Order By: Relevance
“…ESCs were detached from tissue culture dishes using 3 mM EDTA in PBS, and stained according to the following procedure. Cells (3x10 5 ) were incubated with an excess of one of the primary antibodies for 20 min at 4˚C, and then washed twice with washing buffer (PBS containing 2% FCS and 0.1% NaN 3 ). Then, the cells were reacted with FITC-conjugated goat anti-mouse IgG (H+L) (Dako) as a secondary antibody for 20 min at 4˚C, and washed twice.…”
Section: Culture Of Escsmentioning
confidence: 99%
See 1 more Smart Citation
“…ESCs were detached from tissue culture dishes using 3 mM EDTA in PBS, and stained according to the following procedure. Cells (3x10 5 ) were incubated with an excess of one of the primary antibodies for 20 min at 4˚C, and then washed twice with washing buffer (PBS containing 2% FCS and 0.1% NaN 3 ). Then, the cells were reacted with FITC-conjugated goat anti-mouse IgG (H+L) (Dako) as a secondary antibody for 20 min at 4˚C, and washed twice.…”
Section: Culture Of Escsmentioning
confidence: 99%
“…Laminin and type IV collagen (COL-4) are well-known major components of epithelial basement membranes in the human body, and have been reported to localize in the basement membrane structure of human endometrial epithelium (1,2). Several studies have shown that these ECM components are produced at a high level in human deciduas (3,4), while laminin was reported to inhibit endometrial stromal decidualization (5,6). These ECM components were also reported to regulate trophoblast proliferation and differentiation during pregnancy (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Decidualization occurs in response to the ovarian hormones, 17β-estradiol (E2) and progesterone (P4). It is accompanied by the secretion of prolactin and insulinlike growth factor-binding protein-1 (IGFBP-1), and the expression of the gap junction connexin-43 (CX-43) in human ESCs (Brar et al 1995, Yu et al 2011. Decidual ECM remodeling events have also been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that both these ECM components are highly expressed in human endometrial stromal cells and deciduas (3)(4)(5). Laminin has been reported to inhibit endometrial stromal differentiation (6,7), while both laminin and COL-4 have been found to regulate trophoblast proliferation and differentiation during pregnancy (8)(9)(10)(11). Furthermore, abnormal expression of these ECM components in the endometrium was reported in a patient with unexplained infertility (1).…”
Section: Introductionmentioning
confidence: 99%